Conservation of People as a Strategic Factor Influencing the Economic Behavior of the Population - N. D. Kremlev (Статистика и экономика)
The purpose of the study is to determine the strategic factor of saving people, influencing the economic behavior of the population and the sustainable development of the economy. In the modern concept of saving people, the goal of the state is to save, preserve and survive the population by maintaining health, eliminating poverty and unemployment based on an effective policy to enhance economic behavior. Information about people-saving serves not only as an instrument of effective public policy, but also as a way to protect the natural, physiological and socio-economic needs and the economy of a person. However, in the Russian regions, the aging process of the population is intensifying, resulting in a decrease in population, depopulation and urbanization, and there is a significant differentiation in the level of rationality of economic behavior of the population in the regions of the country. According to our hypothesis, overcoming human extinction and barriers to irrational behavior are determined by the main goal of saving the population of Russian regions through effective government policy.The research materials and methods are official statistics data, using the index method, balance constructions, groupings and multifactorial analysis of various data.Research results: the author concludes that the idea of peoplesaving as a strategic factor influencing the economic behavior of the population should become the main goal of public policy, contributing to improving the quality of life of people. The concept of saving people is formulated as processes of change in which the development of personality, the strengthening of current and future human capital, the exploitation of natural resources, the direction of investment, the orientation of scientific and technological progress are coordinated with each other and aimed at meeting the needs of the population. The approbation of the reflection of the factors of people-saving was carried out according to socio-economic indexes for the period 2010-2023, which made it possible to identify positive and negative impacts on the economic behavior of the population, the state’s policy of creating favorable living conditions for people.Conclusion: the use of a statistical approach to reflecting the essence of saving people as a strategic factor will make it possible to activate the economic behavior of the population in many regions of the country by improving the efficiency of resource management. Stimulating rational behavior of the population can lead to an increase in the birth rate, a decrease in mortality, an increase in skilled migration of people, and an improvement in marriage relations. The negative impact of high inflation on the behavior of the population has been established, which artificially reduces the value of people’s labor and knowledge, the purchasing power of money, incomes and household activities. Therefore, the adoption of a new concept of saving people should become a strategic goal of public administration in the regions of the country to improve the well-being of the population.